Judicialization 2.0 : Understanding Right-To-Health Litigation in Real Time - Biehl, Joao (Taylor and Francis, 2019)
Over the past two decades, debate over the whys, the hows, and the effects of the ever-expanding phenomenon of right-to-health litigation (‘judicialization’) throughout Latin America have been marked by polarized arguments and limited information. In contrast to claims of judicialization as a positive or negative trend, less attention has been paid to ways to better understand the phenomenon in real time. In this article, we propose a new approach—Judicialization 2.0—that recognises judicialization as an integral part of democratic life. This approach seeks to expand access to information about litigation on access to medicines (and health care generally) in order to better characterise the complexity of the phenomenon and thus inform new research and more robust public discussions. Drawing from our multi-disciplinary perspectives and field experiences in highly judicialized contexts, we thus describe a new multi-source, multi-stakeholder mixed-method approach designed to capture the patterns and heterogeneity of judicialization and understand its medical and socio-political impact in real time, along with its counterfactuals. By facilitating greater data availability and open access, we can drive advancements towards transparent and participatory priority setting, as well as accountability mechanisms that promote quality universal health coverage.